The Influence of Corporate Social Responsibility, Debt to Equity Ratio, and Total Assets Turnover on Financial Performance of Manufacturing Companies in Indonesia - Lidya Martha; Masyhuri Hamidi; Yurniwati Yurniwati; M Fany Alfarisi (Politeknik Ganesha Medan, 2026)
This study aims to analyse the influence of Corporate Social Responsibility (CSR), Debt to Equity Ratio (DER), and Total Assets Turnover (TATO) on the financial performance of manufacturing companies listed on the Indonesia Stock Exchange during the 2017-2023 period. Financial performance is proxied by Return On Assets (ROA). The population of this study was all manufacturing companies listed on the Indonesian Stock Exchange. The sampling technique used was purposive, with criteria including manufacturing companies that published annual and sustainability reports consistently during 2017-2023 and had complete data for the variables studied. Based on these criteria, 36 manufacturing companies were obtained as the initial sample. After winsorizing extreme DER values and applying a logarithmic transformation, the final sample consisted of 33 companies with 94 unbalanced panel observations. The research method is quantitative, with panel data regression analysis conducted in eviews 12. The best model was selected using the Chow Test, Hausman Test, and Lagrange Multiplier Test, which indicated that the Random Effect Model (REM) was the most appropriate. The key findings indicate that CSR has a positive and significant effect on ROA (p = 0.0273 < 0.05), supporting stakeholder theory. Conversely, DER has a negative and significant effect on ROA (p = 0.0306 < 0.05), suggesting that sample companies have not used debt financing productively. Meanwhile, TATO has no significant effect on ROA (p = 0.0501 > 0.05). This study concludes that CSR and DER are significant determinants of financial performance in opposite directions. at the same time, TATO does not show a direct influence on profitability in the context of Indonesian manufacturing companies during the observation period.